Effect of deterioration of swallowing functions on the frailty status in older adults: a longitudinal cohort study - En-Chih Weng; Yoko Hasegawa; Tasuku Yoshimoto; Ma. Therese Sta. Maria; Koutatsu Nagai; Naoko Sato; Kana Tokumoto; Kazuhiro Hori; Hiroshi Kusunoki; Hiromitsu Kishimoto; Ken Shinmura (BMC Geriatrics)
Abstract Background Deterioration of swallowing function (DSF) is common among aging adults and can lead to negative health outcomes such as increased risk of malnutrition. However, the longitudinal relationship between the DSF and frailty status remains unclear. This study aimed to investigate whether declining swallowing function is linked to frailty progression in independent older adults. Methods This study included 795 community-dwelling Japanese individuals aged ≥ 65 years who participated in two surveys: one at baseline and one after two years. Swallowing function was evaluated using the repetitive saliva swallowing test, tongue pressure test, and questionnaire. DSF was identified by meeting more than one of three criteria: Repeated Saliva Swallow Test below 3, tongue pressure under 27.4 kPa for men and 26.5 kPa for women, and a “yes” response to the questionnaire. Frailty status was assessed using the Kihon Checklist, with participants showing a decline categorized into the “aggravation group.” Oral function (number of teeth, occlusal force, masticatory performance, and oral dryness) and physical function (body mass index, gait speed, grip strength, and skeletal muscle mass index) were evaluated. Comparisons between the two groups were made using the Student’s t-test or the χ2 test. Differences among the three groups were assessed using the one-way analysis of variance or the χ2 test. Significant differences in continuous variables were analyzed using the Least Significant Difference method, with P-values adjusted using the Bonferroni correction. Results Initially, 87 (10.9%) participants were frail. By follow-up, 149 participants (37.9%) had progressed to frailty, 83 of whom (55.7%) exhibited impaired swallowing function at baseline. At baseline, frailty was significantly associated with age, gait speed, decreased swallowing function, number of functional teeth, occlusal force, and masticatory performance. None of the three swallowing function assessment methods were significantly associated with the progression of frailty. In contrast, logistic regression analysis of frailty progression showed that impaired swallowing function was a significant explanatory variable (OR, 1.53; 95% CI: 1.04–2.21). Conclusion This study found a significant association between frailty and multiple factors, particularly oral function. Specifically, diminished swallowing function has emerged as a notable independent predictor of frailty progression.